The Impact of Mindset on Self-Tracking Experience - Hancı, Elçin; Ruijten, Peter A. M.; Lacroix, Joyca; IJsselsteijn, Wijnand A. (Frontiers in Digital Health, 2021)
Self-tracking technologies aim to offer a better understanding of ourselves through data, create self-awareness, and facilitate healthy behavior change. Despite such promising objectives, very little is known about whether the implicit beliefs users may have about the changeability of their own behavior influence the way they experience self-tracking. These implicit beliefs about the permanence of the abilities are called mindsets; someone with a fixed mindset typically perceives human qualities (e.g., intelligence) as fixed, while someone with a growth mindset perceives them as amenable to change and improvement through learning. This paper investigates the concept of mindset in the context of self-tracking and uses online survey data from individuals wearing a self-tracking device (n = 290) to explore the ways in which users with different mindsets experience self-tracking. A combination of qualitative and quantitative approaches indicates that implicit beliefs about the changeability of behavior influence the extent to which users are self-determined toward self-tracking use. Moreover, differences were found in how users perceive and respond to failure, and how self-judgmental vs. self-compassionate they are toward their own mistakes. Overall, considering that how users respond to the self-tracking data is one of the core dimensions of self-tracking, our results suggest that mindset is one of the important determinants in shaping the self-tracking experience. This paper concludes by presenting design considerations and directions for future research.